ANALISIS MANFAAT INFORMASI AKUNTANSI PADA UKM DI WILAYAH TANGGULANGIN - Andreas Failian; Pepie Diptyana (The Indonesian Accounting Review, 2012)
It has been the fact that the main objective of a business is to get profit as much as possible and so does the business of small and medium enterprises (SMEs). Besides that, the business should be able to reduce unemployment in a country. This study tries to determine the benefits of accounting information for small and medium businesses. It is a qualitative and ethnography type. The qualitative data were derived from internal data sources, using three methods, namely observation, interviews, and documentation. The analytical techniques was used is to compare the theory with the results of interviews on the informants of five persons, in which they were the owner and managers of SMEs. Their average monthly income is 10 million rupiahs. The benefits of accounting information is a source of data to control the performance of SMEs and for consideration for decisions, in which accounting information is used for internal party SMEs and not for external parties SMEs. Barriers faced by SME owners and managers are on the knowledge and ability in applying accounting in SMEs, so these should be taken seriously into account in accounting so that they can understand about accounting.